A randomized controlled trial of a tablet‐based intervention to address predonation fears among high school donors. Issue 7 (14th April 2020) - France, Christopher R.; France, Janis L.; Kowalsky, Jennifer M.; Conatser, Robert; Duffy, Louisa; Barnofsky, Natalie; Kessler, Debra; Shaz, Beth
Abstract : BACKGROUND: Prior studies have shown donation‐related fear to be associated with decreased donor confidence and an increased risk for vasovagal reactions. This study examined the effects of a predonation intervention that provided fearful donors with suggestions for coping. STUDY DESIGN AND METHODS: Using a tablet‐based application, high school donors (49.4% female) answered a question regarding their fear of having blood drawn. Those who reported fear were randomly assigned to either a control (n = 930) or an intervention (n = 911) group. Donors in the control group rated their confidence in dealing with their fear and then donated as usual. Donors in the intervention group received a brief audiovisual presentation on coping strategies, rated their confidence, and then donated as usual. RESULTS: A higher proportion of fearful versus nonfearful donors experienced a vasovagal reaction, even after controlling for other demographic and health predictors (OR, 2.3; 95% CI, 1.655‐3.185, p < 0.001). Fearful donors who received the intervention reported greater confidence than controls, but the proportion of vasovagal reactions did not differ significantly between the intervention (6.1%) and control (6.8%) groups. CONCLUSION: Although the current tablet‐based intervention may have some psychological benefit in that it was associated with greater donor confidence, the observed effect was small and did not translate into a lower risk for vasovagal reactions. However, greater confidence among young donors may lead to an increased willingness to donate again—a potential outcome that we will revisit among these donors as part of a planned 2‐year follow‐up. Abstract : See editorial on page 1340–1342, in this issue